(untitled) (Zaporizhzhia Historical Review, 2021)
This article is dedicated to the investigation of methods of Pontic expansion in the Nothern part of the Black Sea region. Different diplomatic instruments used by Mitridad Evpator for the creation of his control in this region were studied in details. Different approaches in the treatment policy towards the barbaric tribes and Greek population were differentiated and researched.